Комплексний комбінований прогрів: системний підхід до формування схем забезпечення оптимального температурного стану ТЗ в умовах експлуатації - Грицук, Ігор Валерійович (НТУ "ХПІ", 2015)
The article describes the results of the formation of a systematic approach to ensure optimal temperature condition of the vehicle in service with the help of a complex combined with warm thermal storage technology. The prevailing approach allows the system to explore all possible schemes integrated system for combined heating motor vehicle and (or) power plant arising from patterns (morphology) structure. This approach takes into account, besides the already known and unusual options that under normal bust could be neglected. This, unlike the simple enumeration is eliminated undesirable option skip any options. This is an opportunity to consider the long–term technical solutions while still in the stages of design and technological development, or those who currently do seem inconsistent to study the processes of warming up the engine.
Complex combined heating: a systematic approach to the formation of schemes to ensure optimal temperature condition of vehicles in operation
Keywords: охолоджуюча рідина; моторна олива; система мащення; двигуни внутрішнього згорання; vehicle; power plant operation; system approach; optimal thermal condition; heat storage